2018
DOI: 10.3390/publications6030037
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Concerns in the Rise of Co-Authorship and Its Role as a Proxy of Research Collaborations

Abstract: Increasing specialization, changes in the institutional incentives for publication, and a host of other reasons have brought about a marked trend towards co-authored articles among researchers. These changes have impacted Science and Technology (S&T) policies worldwide. Co-authorship is often considered to be a reliable proxy for assessing research collaborations at micro, meso, and macro levels. Although co-authorship in a scholarly publication brings numerous benefits to the participating authors, it has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 50 publications
0
28
0
3
Order By: Relevance
“…Many previous authors have suggested that requiring contributions to be spelled out reduces "honorary" authorship, in which researchers (typically senior ones) are listed as co-authors despite not satisfying the extant criteria [10][11][12][13]. This may be true, and superficially this would be good because honorary authorship is a dishonest practice.…”
Section: Benefits Of a Contributorship Model With A Standardized Taxomentioning
confidence: 99%
“…Many previous authors have suggested that requiring contributions to be spelled out reduces "honorary" authorship, in which researchers (typically senior ones) are listed as co-authors despite not satisfying the extant criteria [10][11][12][13]. This may be true, and superficially this would be good because honorary authorship is a dishonest practice.…”
Section: Benefits Of a Contributorship Model With A Standardized Taxomentioning
confidence: 99%
“…Co-authorship is a process in which two or more authors share their talents and sources by adopting one of the cooperation methods and begin a collaboration to create a scientific work. One method that is used in probing the co-authorship collaboration is drawing co-authorship networks and its analysis (Koseoglu, Okumus, Putra, Yildiz, & Dogan, 2018;Kumar, 2018;Sonnenwald, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Many previous authors have suggested that requiring contributions to be spelled out reduces "honorary" authorship, in which researchers (typically senior ones) are listed as co-authors despite not satisfying the extant criteria [10][11][12][13]. This may be true, and superficially this would be good because honorary authorship is a dishonest practice.…”
mentioning
confidence: 99%